Covariant Canonical Method for Yang-Mills Theory Expressed as a Constrained BF-Like Theory - Alberto Escalante; Irving García (Advances in Mathematical Physics)
The covariant canonical analysis for Yang-Mills theory expressed as a BF-like action is performed. We study a BF-like action, that in spite of being the coupling of two topological terms, yield, on shell to Yang-Mills action. In addition, by using the results obtained in the covariant canonical approach we study the symmetries of the action, in particular we calculate its energy-momentum tensor obtaining the same tensor found for Yang-Mills theory; then we confirm those results by using Noether's theorem.